The Determinants of Economic Growth in Selected Arab Countries over the Period 1998-2017 - Alhaj Yousef, Elham; Warrad, Taleb (Jordan Journal of Economic Sciences, 2020)
This paper aims at exploring the main determinants of economic growth in Arab countries (AC) by shedding light on the most effective determinants. The study uses panel data for twelve Arab countries over the period from 1998 to 2017. Some of the study variables are stationary at level and the others are not. Kao and Pedroni Panel Cointegration tests showed that the models were cointegrated. Therefore, Fully Modified OLS (FMOLS) model was applied for estimation, which revealed that labor force growth rate, gross fixed capital formation, trade openness, economic freedom and most governance indicators were significantly and positively related to economic growth of AC over the study period. The study recommends that in order to boost the economic performance, Arab governments need to promote and increase investments in fixed and human capital, focus on manufacturing and exporting goods where comparative advantage is existed, diversify their production, enhance the rule of law, and encourage the national cohesiveness and peaceful coexistence that ensure political and social stability.